Platelet‐Derived Growth Factor‐BB Protects Mesenchymal Stem Cells (MSCs) Derived From Immune Thrombocytopenia Patients Against Apoptosis and Senescence and Maintains MSC‐Mediated Immunosuppression. (28th July 2016) - Zhang, Jia-min; Feng, Fei-er; Wang, Qian-ming; Zhu, Xiao-lu; Fu, Hai-xia; Xu, Lan-ping; Liu, Kai-yan; Huang, Xiao-jun; Zhang, Xiao-hui
Abstract : Immune thrombocytopenia (ITP) is characterized by platelet destruction and megakaryocyte dysfunction. Platelet‐derived growth factor (PDGF) improves growth and survival in various cell types and promotes mesenchymal stem cell (MSC) proliferation. PDGF‐BB protects MSCs derived from ITP patients against apoptosis, senescence, and immunomodulatory defects. This protective effect of PDGF‐BB is likely mediated via the p53/p21 pathway, thus potentially providing a new therapeutic approach for ITP. Abstract: Immune thrombocytopenia (ITP) is characterized by platelet destruction and megakaryocyte dysfunction. Mesenchymal stem cells (MSCs) from ITP patients (MSC‐ITP) do not exhibit conventional proliferative abilities and thus exhibit defects in immunoregulation, suggesting that MSC impairment might be a mechanism involved in ITP. Platelet‐derived growth factor (PDGF) improves growth and survival in various cell types. Moreover, PDGF promotes MSC proliferation. The aim of the present study was to analyze the effects of PDGF‐BB on MSC‐ITP. We showed that MSC‐ITP expanded more slowly and appeared flattened and larger. MSC‐ITP exhibited increased apoptosis and senescence compared with controls. Both the intrinsic and extrinsic pathways account for the enhanced apoptosis. P53 and p21 expression were upregulated in MSC‐ITP, but inhibition of p53 with pifithrin‐α markedly inhibited apoptosis and senescence. Furthermore, MSCs from ITP patients showed a lower capacity for inhibiting the proliferation of activated T cells inducing regulatory T cells (Tregs) and suppressing the synthesis of anti‐glycoprotein (GP)IIb‐IIIa antibodies. PDGF‐BB treatment significantly decreased the expression of p53 and p21 and increased survivin expression in MSC‐ITP. In addition, the apoptotic rate and number of senescent cells in ITP MSCs were reduced. Their impaired ability for inhibiting activated T cells, inducing Tregs, and suppressing the synthesis of anti‐GPIIb‐IIIa antibodies was restored after PDGF‐BB treatment. In conclusion, we have demonstrated that PDGF‐BB protects MSCs derived from ITP patients against apoptosis, senescence, and immunomodulatory defects. This protective effect of PDGF‐BB is likely mediated via the p53/p21 pathway, thus potentially providing a new therapeutic approach for ITP.